2011
DOI: 10.5296/npa.v3i2.819
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Preference in GMPLS-controlled Wavelength Switched Optical Networks

Abstract: Given the potentialities in terms of high bandwidth, low costs, and low power consumption, Wavelength Switched Optical Networks (WSONs) are the most promising candidate for next generation backbone networks. In WSONs the optical signal is switched at the wavelength granularity, therefore the wavelength assignment process plays a crucial role in dynamic network operation.Generalized Multi-Protocol Label Switching (GMPLS) is the standard control plane for WSONs. However, current GMPLS protocol suite does not env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In [14], a review of several strategies that employs the suggested vector approach is presented, including both, ROADMs with and without wavelength conversions.…”
Section: Related Workmentioning
confidence: 99%
“…In [14], a review of several strategies that employs the suggested vector approach is presented, including both, ROADMs with and without wavelength conversions.…”
Section: Related Workmentioning
confidence: 99%
“…As feasible approach, each sub problem is solved separately in most of existing works [13]. Architecture of control plane performing the route and wavelength selection is also discussed [14]. There are many possible solutions to the RWA problem [15].…”
Section: A Routing and Wavelength Assignmentmentioning
confidence: 99%